Kepemimpinan Profetik dalam Manajemen Pendidikan: Studi tentang Taujîh dan Tansîq Berbasis Literatur Hadis - Ridho, Muhammad; Sagir, Ahmad; Ansari, Adi (Murid: Jurnal Pemikiran Mahasiswa Agama Islam, 2026)
Prophetic leadership in Islamic educational management represents a transformational paradigm that integrates divine values ​​with modern administrative practices. This study analyzes the concepts of taujîh (orientation/direction) and tansîq (harmonization/coordination) based on hadith literature as the foundation of educational leadership. Through a systematic literature review method of leadership hadiths, the study found that prophetic taujîh emphasizes a moral-spiritual vision that integrates falah (worldly and afterlife) while tansîq prioritizes structural harmony based on brotherhood and deliberation. This model offers an alternative to the secular managerial approach that tends to be instrumental-rational by actualizing ad-din as the totality of the educational system. The results of the analysis show that the synthesis of taujîh-tansîq in the hadith treasury forms a leadership of syajâ'ah (moral courage) that is able to bridge the goals of Islamic epistemology with the dynamics of contemporary educational organizations. The theoretical implications provide an ontological basis for the development of educational leadership based on the revelation and scientific tradition of the Prophet Muhammad ﷺ.